ANALISIS PERBEDAAN STRATEGI DIVERSIFIKASI QUIPPER DAN RUANG GURU - Larissa, Jesslyn; Yang, Jenny; Nicholas, Nicholas; Susanti, Oktris; Yuki, Narumi (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
Ruangguru and Quipper are well-known education service technology companies.A diversification strategy is a strategy used by the company to expand its productswith the aim of increasing business so that the business can experience growth andan increase in sales. The purpose of conducting this research is to analyze thedifferences in the implementation of the business strategy implemented byRuangguru and Quipper. This study used a descriptive writing method on data onthe implementation of Ruangguru and Quipper's diversification strategy.